2016
DOI: 10.3389/fpls.2016.01499
|View full text |Cite
|
Sign up to set email alerts
|

Cytomolecular Analysis of Ribosomal DNA Evolution in a Natural Allotetraploid Brachypodium hybridum and Its Putative Ancestors—Dissecting Complex Repetitive Structure of Intergenic Spacers

Abstract: Nucleolar dominance is an epigenetic phenomenon associated with nuclear 35S rRNA genes and consists in selective suppression of gene loci inherited from one of the progenitors in the allopolyploid. Our understanding of the exact mechanisms that determine this process is still fragmentary, especially in case of the grass species. This study aimed to shed some light on the molecular basis of this genome-specific inactivation of 35S rDNA loci in an allotetraploid Brachypodium hybridum (2n = 30), which arose from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 73 publications
1
30
0
Order By: Relevance
“…At the level of interphase nuclei, additional markers such as species-specific intergenic spacers (IGSs) and chromosome-specific BAC clones are required to differentiate these loci. It was documented by FISH with either chromosome-specific BACs or IGSs along with 25S rDNA as probes that only B. distachyon -like loci associate with the nucleolus in the B. hybridum nuclei isolated from roots 24 .
Figure 1DNA methylation patterns of 35S rRNA genes in B. hybridum . (a) FISH with 25S rDNA (red fluorescence) as a probe in the representative interphase nucleus of B. hybridum (genotype ABR113).
…”
Section: Results and Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the level of interphase nuclei, additional markers such as species-specific intergenic spacers (IGSs) and chromosome-specific BAC clones are required to differentiate these loci. It was documented by FISH with either chromosome-specific BACs or IGSs along with 25S rDNA as probes that only B. distachyon -like loci associate with the nucleolus in the B. hybridum nuclei isolated from roots 24 .
Figure 1DNA methylation patterns of 35S rRNA genes in B. hybridum . (a) FISH with 25S rDNA (red fluorescence) as a probe in the representative interphase nucleus of B. hybridum (genotype ABR113).
…”
Section: Results and Disscussionmentioning
confidence: 99%
“…The isolation was performed as described 24 . Briefly, 40 seedlings were fixed in 4% formaldehyde in 1 × PBS (pH 7.3) for 30 min at 4 °C and washed in 1 × PBS for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the whole genomic sequence of both diploid progenitors and several B. hybridum genotypes is available for the scientific community (IBI, 2010, https:// phytozome.jgi.doe.gov). The preferential silencing of the B. stacei-like rDNA loci was documented in different tissues of B. hybridum, including both meristematic (Idziak and Hasterok, 2008) and differentiated (Borowska-Zuchowska et al, 2016) root cells, prophase-I meiocytes, microspores and different tissues of immature and imbibed embryos (Borowska-Zuchowska et al, 2019). As yet, there have been no reports on the expression status of the S-genome rRNA genes in B. hybridum leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Nucleoli are sites of transcription of rRNA, which is participating in the ribosome assembly. A typical feature of ND is that ribosomal genes inherited from one (dominant) parental species are expressed and those inherited from the other parent are silenced (Neves et al, 1997;Lawrence et al, 2004;Idziak and Hasterok, 2008;Ksiazczyk et al, 2011;Borowska-Zuchowska et al, 2016). Expression analysis of the rRNA transcription in two yeast strains revealed that the proportion of active rDNA is regulated by a dosage control mechanism (French et al, 2003).…”
Section: Genome and Nucleolar Dominancementioning
confidence: 99%